Technopreneur Design of Marine Aquaculture Based on Multi-Trophic Aquaculture and Tfd-Bakar Batu for Millennials in the Era of Digital Society in Tablolong Kupang Ntt - Daniel Wadu; Aplonia Bani; Deselina Kaleka; Boimau Pither; A Pakro (Journal of Social Research, 2023)
Integrated multi-trophic aquaculture (IMTA) is an innovation from conventional cultivation methods or focusing on one species to integrated cultivation of several species together. This study aims to design an entrepreneurial model for technology-based millennials by combining Integrated Multi-trophic Aquaculture (IMTA) and downstream "TFD-Bakar Batu" as a technology for handling agricultural products with a collaboration system through partnership efforts in Tablolong waters, Kupang Regency, East Nusa Tenggara Province. Stakeholder perceptions of the model design are centered on several issues such as risk, impact on the use of marine space, and the level of acceptance of fishermen, millennials so that this model can be socially accepted with the level of stakeholder satisfaction. The method used in this study uses questionnaires conducted on provincial governments, district governments, the private sector, communities and fishermen to identify potential and stakeholder concerns and perceived benefits at the commercial production level, with research questions on the level of understanding of IMTA, spatial location problems, food safety and disease, waste utilization and the emergence of new economic sectors. Data was analyzed using qualitative data analysis with NVivo14 QSR International software. The results showed that there are several problems including risks to the environment, risks arising from governance and risks to the industry itself however, stakeholders feel that the source of risk can be overcome with agricultural product handling technology "TFD Bakar Batu" and policies. Stakeholders also believe that this model can contribute to improving the aquaculture industry so that this model can develop from pilot scale to industrial scale through studies by forming entrepreneurs using technology.